Analisis Cerpen “Finja’anu Qahwati Baridun” Karya Ihsan ‘Abd Al-Quddus - Bahtiyar Yusuf; Abdul Latif (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2019)
Research on Gramscian Hegemony in short stories "Finja'anu Qahwati Baridun (A Cup of Cold Coffee)" the work of Ihsan 'Abd al-Quddus aims to explain the ideological formation that operates in the short story "Finja'anu Qahwati Baridun (A Cup of Cold Coffee)" and how the practices of hegemony are carried out. This research is a qualitative description research. The data in this study are the text contained in the short story "Finja'anu Qahwati Baridun (A Cup of Cold Coffee)." The data source used in this study is the short story "Finja'anu Qahwati Baridun (A Cup of Cold Coffee) "The work of Ihsan 'Abd al-Quddus. Data collection in this study was carried out by reading, recording and processing research data. The results obtained from this study are idelological formations which operate in the short story "Finja'anu Qahwati Baridun (A Cup of Cold Coffee)" conducted by several figures, namely feudalism, socialism. Practices - Hegemony practices are divided into two groups, namely groups lay (who maintains power) and rebel groups (who fight for power). From the results of the analysis the author uses the theory of hegemony which was triggered by Gramsci. In this case it can be concluded that the practice of hegemony is inseparable from the counter hegemony. Ideology formation is needed to subvert the power and practices of the Hegemony carried out on two groups, namely the lay group / community and rebel groups.